Effect of dietary mannan-oligosaccharides from copra meal on intestinal microbes and blood profile of broiler chickens - Putri, A. N. S.; Sumiati, S.; Meryandini, A. (Diponegoro University, 2017)
Mannan-oligosaccharides (MOS) is a common prebiotics used as a feed additives. The use of antibiotic can be replaced by MOS to reduce the number of pathogenic bacteria in small intestines of chickens. The objective of this study was to determine the effect of MOS extracted from copra meal on intestinal microbial population and blood profile of broiler chickens. The study was conducted by using 150 day-old male broiler chickens (average body weight 46.00 + 1.41 g). The design of this experiment was a completely randomized design (CRD) with 3 dietary treatments, 5 replications and 10 birds in each replication. The dietary treatments consisted of control diet (corn-soybean meal diet without supplementation of antibiotic and prebiotic), control + 0.1% antibiotic bambermycin, and control + 0.035% MOS. For the first 4 weeks the birds were fed treatment diets, followed by commercial feed for 2 weeks. The parameters observed in this study were intestinal microbes population and blood profiles. The results showed that the administration of 0,035% MOS increased the lactic acid bacteria (LAB) number compared with antibiotics feed (P<0.05), but not significantly different (P >0.05) with the control group. The total aerobic and coliform bacteria were higher in MOS and antibiotic treatment compared than control group. The supplementation of 0.035% MOS from copra meal in diet increased the level of leucocytes which is important to immune response of broilers and its usage was safe because the level of chicken blood profile were within the normal range.